Creativity in children’s speech development: a case study of Persian speaking children - Samad Mirza Suzani (Journal of Child Language Acquisition and Development)
This study aimed to investigate the innovations in speech development of Persian speaking children based on naturalistic paradigms of child language research. To this end, following a longitudinal observation approach, the naturalistic and experimental aspects of child language acquisition were examined as it was considered to have the advantage of producing spontaneous natural data. The data consisted of utterances by a number of children at an age range of 1;10 to 4;10 since it is considered a productive period for the creation of new words. The participants of the study included the researcher's own son, his brother-in-law's son, his niece and nephew, his neighbors' children, as well as a few children from a child-care center in Noshahr, Iran. To investigate the innovations in speech development of these children, instances of deletion, substitution, and inversion as well as creative processes such as making negative verbs, innovative rule-making in the utterances, and rule-overgeneralizing for inserting inflections were collected and recorded. The findings of this study chiefly support Clark's (1981) argument that creativity in children's speech results from the need of finding an acceptable word to fill a gap in the lexicon. Moreover, the findings confirm Lust’s (2006) claim that children rely on their creative theory construction as a compensatory tool and productive device to create new words. Alternatively, the innovations that do not conform to the adult forms indicate that children have not learned the exceptions to the rules and less productive inflections conveying the same meaning; or may tend to convey the message from their own perspectives and to encode the events accordingly. The small sample used was a limitation of this study, nonetheless to arrive at broader generalizations, more supporting evidence from conducting studies on children’s differences, their social interaction with others, and the role of linguistic input are recommended.